Phosphate fertilization in a corn-Urochloa intercrop system - Serifo dos Santos, Brás; Moraes Guimarães, Tiara; Tardin Pinheiro Bezerra, Aracy Camilla; Hideo Martins da Costa, Claudio; Hortêncio Mota, José (Revista Ceres, 2025)
Corn intercropped with Urochloa contributes not only to increasing soil coverage but also to improving physical, biological, and chemical quality, especially in Cerrado soils that have low phosphorus availability. Therefore, the objective of this work was to evaluate the response of different doses of phosphorus (P) in production systems on the chemical attributes of the soil, and physiological, biometric, and productive parameters of corn. Thus, an experiment was conducted with a randomized block design in a split-plot scheme, with four replications. The plots consisted of two production systems: single corn and intercropped corn. The subplots consisted of three doses of phosphorus. Soil chemical attributes, gas exchange, chlorophyll content, biometric components, and corn productivity were evaluated. The physiological parameters were not affected by the systems and P doses. In the biometric components, there was a significant effect only for stalk diameter, where corn in the single system had a larger diameter in comparison to the intercropped one. There were effects for P contents in the system and dose factors, while for organic matter and carbon only in the dose factor. Production systems and phosphate fertilizer did not influence corn grain productivity